The Role of Theory in Forming Economic Policy: A Growth Theory Perspective - Wahyuni, Sri; Harahap, Isnaini; Nawawi, Zuhrinal M (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research explores the role of economic growth theory in policy formation. In the introduction, it is highlighted the importance of understanding economic theory to achieve macroeconomic goals and how economic growth theory is the basis for the policy formation process. The research method uses a literature review and systematic literature review (SLR) approach to review growth theories from various sources such as journals, articles, and textbooks. The results show diverse views of related research, highlighting the importance of different methodological approaches. Key findings include 13 significant journals, the most active researchers, research topics, and methods used. This research confirms that understanding economic growth theory is a crucial foundation for the formation of successful economic policies and has a positive impact on a country's economic development.